2005
DOI: 10.1177/001440290507100403
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Peer Interactions for Students with Severe Disabilities via Paraprofessional Training

Abstract: As students with severe disabilities are included in general education settings, the use of paraprofessionals has expanded to meet these students' needs. Unfortunately, paraprofessionals can have the inadvertent effect of intensifying the social isolation of students with disabilities. This study investigated the effectiveness of a training program aimed at teaching four paraprofessionals to facilitate interactions between students with severe disabilities and their peers. A multiple baseline, single-subject d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 29 publications
2
53
0
2
Order By: Relevance
“…Research has shown, however, that this resource is often misused and the results on socialization, particularly, are detrimental to the students (Giangreco, Edelman, Luiselli, & MacFarland, 1997;Malmgren, & Causton-Theoharis, 2006). With very little in-service, an educational assistant is able to make a significant difference to peer interactions and socialization (Causton-Theoharis & Malmgren, 2005). Among the strategies/accommodations that an educational assistant can provide for a student with ASD in the classroom are: -Increasing physical proximity to peers -Fading assistance to allow for more natural peer interaction opportunitiesPartnering student with ASD with peers during academic tasks -Verbally highlighting similarities between student with ASD and peers -Creating communication cards focused on social exchanges -Teaching peers how to communicate with target student using sign language gestures -Utilizing interactive technology -Giving student with ASD classroom responsibilities that encourage interaction with peers (Causton-Theoharis, J., & Malmgren, 2005, p. 436) Social skills training programs are another possible response to the need for individualized training in reciprocal play and conversational skills for children with ASD.…”
Section: Fostering Genuine Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown, however, that this resource is often misused and the results on socialization, particularly, are detrimental to the students (Giangreco, Edelman, Luiselli, & MacFarland, 1997;Malmgren, & Causton-Theoharis, 2006). With very little in-service, an educational assistant is able to make a significant difference to peer interactions and socialization (Causton-Theoharis & Malmgren, 2005). Among the strategies/accommodations that an educational assistant can provide for a student with ASD in the classroom are: -Increasing physical proximity to peers -Fading assistance to allow for more natural peer interaction opportunitiesPartnering student with ASD with peers during academic tasks -Verbally highlighting similarities between student with ASD and peers -Creating communication cards focused on social exchanges -Teaching peers how to communicate with target student using sign language gestures -Utilizing interactive technology -Giving student with ASD classroom responsibilities that encourage interaction with peers (Causton-Theoharis, J., & Malmgren, 2005, p. 436) Social skills training programs are another possible response to the need for individualized training in reciprocal play and conversational skills for children with ASD.…”
Section: Fostering Genuine Relationshipsmentioning
confidence: 99%
“…A possible response to this problem is through the use of predetermined scripts. Pre-determined scripts teach children with ASD role-specific dialogue in socio-dramatic play situations (Causton-Theoharis, J., & Malmgren, 2005;Charlop-Christy & Kelso, 2003;Thiemann & Goldstein, 2001). Activities can be incorporated into the inclusive classroom in which the whole student population participates in dramatic role-playing activities.…”
Section: Fostering Genuine Relationshipsmentioning
confidence: 99%
“…Par exemple, une élève de cinquième année n'osait pas parler à Juliette, qui présente une déficience intellectuelle, parce que, selon son témoignage, l'AE l'interrogeait sur ses intentions chaque fois qu'elle s'approchait de sa camarade. En limitant les interactions entre les élèves identifiés comme EHDAA et les autres élèves des classes ordinaires, les AE freinent l'élan naturel des enfants à développer des liens d'amitié avec ceux qui en ont souvent le plus besoin (Causton-Theoharis et Malmgren, 2005b). Par ailleurs, le niveau d'engagement des enseignants à l'égard des élèves identifiés comme EHDAA peut être compromis quand ils ne parviennent pas à travailler de concert avec leurs collègues AE dont ils ne comprennent pas le rôle ni les responsabilités, notamment quand ils commencent leur carrière d'enseignant (Giangreco, 2003).…”
Section: Quant à L'application De Méthodes Douteusesunclassified
“…When utilised properly these individuals can provide a beneficial support structure for inclusion (Giangreco, 2010). Nonetheless, untrained or inappropriately used paraprofessionals may lead to negative experiences (Causton-Theoharis & Malmgren, 2005), such as the promotion of learned helplessness among the SwD. Moreover, the use of paraprofessionals in the classroom can in some cases impede peer interactions (Rutherford, 2012), and social and academic growth (Giangreco & Broer, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of paraprofessionals in the classroom can in some cases impede peer interactions (Rutherford, 2012), and social and academic growth (Giangreco & Broer, 2005). While the effect and the role of the paraprofessional in HPE settings has been studied in other countries such as the United States of America (Tews & Lupart, 2008;Causton-Theoharis & Malmgren, 2005;Horton, 2001;Stilwell, 1995;Thompson & Edwards, 1994;Vogler, French, & Bishop, 1989;Trame, 1982;Hardy, 1980), we were unable to find any paraprofessional literature specific to HPE environments emanating from Australia data. Nonetheless, these prior studies have only considered perspectives of paraprofessional support based upon SwD and their parents, neglecting the HPE teachers' perceptions.…”
Section: Introductionmentioning
confidence: 99%